A critical review of current water use in Magadi Township, Kenya with recommendations for long term sustainable management practices - Chimoyi, Lucy Andere (My University, 2010)
In recent years, Magadi Soda Company has experienced short supplies of water to the company and the Township. This problem has been caused by a prolonged dry spell coupled with the installation and commissioning of a new fly ash plant and an increase in the population of Magadi Township. Water rationing to the Township residents as well as the local community surrounding the Township was introduced by the Water Development Committee as a short term sustainability measure in 2005 to ensure a continuous supply of water to the processing plants. The effectiveness of this rationing as part of a water conservation strategy has been assessed and it has been established that a long term sustainability plan is needed to co-ordinate water demand and supply in Magadi. This study looked at the current water use in Magadi Township while trying to establish a relationship between the number of occupants in each household, the class of housing in Magadi Township and the daily consumption of water. To achieve this, data was collected in three stages: site visits, interviews with company representatives and interviews with the Township residents by use of questionnaires. Site visits were performed to understand the intricacies in the water distribution network. The outcome of the interviews with the company representatives presented some of the problems that led to the implementation of the rationing program and the current issues the company faces as a result of implementing the program. The interviews with the Township residents indicated that the high demand for water was as a result of the high number of people who depend on Magadi Soda Company for water.The study reveals that the amount of water consumed in the Township during the dry and wet seasons was not significantly different and the daily water consumption throughout the weeks was constant. The number of occupants determined the amount of water consumed daily in each household. In addition, the households in the upper class housing were seen to consume more water daily than the households in the middle and lower class despite having the least number of occupants. The daily domestic activity that consumed a lot of water in Magadi Township was the irrigation of gardens which was mostly practised in the upper class households. Several options for improving the long term sustainability of water supply to the local community, Township residents and the Magadi Soda Company processing plants are discussed. The options considered explore the possibility of using alternative sources of water such as stormwater, greywater and desalination to supplement the current water supply to Magadi. These options need to be both cost effective and practical. Proper management of water was one of the solutions discussed with the company representatives in averting a water crisis in the future. A water monitoring program should be formulated to monitor the distribution system of water in Magadi. This includes minimising wastage of water and penalising residents who fail to adhere to such measures, creating awareness on the appropriate use of water by conducting educational campaigns to all the residents of Magadi, installation of technologically advanced plumbing appliances and fittings in the households such as low flush toilets and proper maintenance of the existing water infrastructure to prevent water losses through leaks caused by faulty and worn out infrastructure.